Analisis Pengelolaan Usaha Kolam Pancing Tinjauan Hukum Islam - Daniel Pratama Ramadhan; Jumni Nelli; Ahmad Adri Riva'i (MUI Kota Pekanbaru, 2025)
In practice, anglers are required to purchase one kilogram of fish before starting fishing, then the fish are released into a pond shared with other anglers. This provision creates the potential for uncertainty (gharar), especially because the catch is not always comparable to the fish that have been purchased, or even nothing at all. This practice is highlighted from the perspective of Fiqh Muamalah because it concerns the validity of the contract and the element of justice in the transaction. The aim of this study is to determine the management practices of the Ocu Kampar fishing pond and to analyze the Fiqh Muamalah perspective on these practices. This study is a descriptive qualitative study, with data collection methods in the form of observation, interviews with 10 informants (owners and visitors of the pond), and documentation. The results of the study indicate that the implemented system contains elements of gharar because there is uncertainty between the price paid and the benefit (fish obtained). According to Islamic jurisprudence (Fiqh Muamalah), a sale and purchase must be based on the clarity of the object of the contract, the willingness of both parties, and be free from uncertainty and speculation. Therefore, the practice of managing the fishing pond does not align with Islamic muamalah principles, and the system needs to be improved to comply with sharia, such as clearly separating the sale and purchase contracts from the lease and eliminating the element of uncertainty regarding the number of fish.